2017
DOI: 10.1038/s41598-017-05071-z
|View full text |Cite
|
Sign up to set email alerts
|

Phenomenological Model for Defect Interactions in Irradiated Functional Materials

Abstract: The ability to tailor the performance of functional materials, such as semiconductors, via careful manipulation of defects has led to extraordinary advances in microelectronics. Functional metal oxides are no exception – protonic-defect-conducting oxides find use in solid oxide fuel cells (SOFCs) and oxygen-deficient high-temperature superconductors are poised for power transmission and magnetic imaging applications. Similarly, the advantageous functional responses in ferroelectric materials that make them att… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 61 publications
0
6
0
Order By: Relevance
“…As a result, the peak is shifted to lower frequency. Nevertheless, newly formed oxygen vacancies resulting from excessive Mn doping (i.e., 2 mol%) may strengthen the defect interaction and increase the number of mobile V O ¨. Thus, the peak is back to higher frequency.…”
Section: Resultsmentioning
confidence: 99%
“…As a result, the peak is shifted to lower frequency. Nevertheless, newly formed oxygen vacancies resulting from excessive Mn doping (i.e., 2 mol%) may strengthen the defect interaction and increase the number of mobile V O ¨. Thus, the peak is back to higher frequency.…”
Section: Resultsmentioning
confidence: 99%
“…The γ‐ray radiation will induce trapped defects and compensate a part of internal defects, resulting in a weakened domain unpinning effect. Meanwhile, the radiation effect should be influenced by domain size, orientation, grain boundary density, and morphology, as reported by Brewer et al The different ratios of phase structure and grain boundary in HfAlO‐20 thin films may induce a relative change during fatigue tests, as shown in Figure c.…”
Section: Resultsmentioning
confidence: 68%
“…It has verified that interface defects have been formed in the TiN/HfO2/Si MOS capacitor during irradiation, and the accumulation capacitance decreased with the increasing of irradiation dose [13]. Brewer et al indicated that the radiation effect can be also influenced by orientation, domain size, grain boundary density and morphology [14][15]. C. Palade et al [16] demonstrated that the trilayer of control HfO2/floating gate of Ge nanoparticles in HfO2/tunnel HfO2/Si substrate containing HfO2 nanocrystals with the orthorhombic/tetragonal structure has a high sensitivity of 0.8 mV Gy −1 to α particle irradiation.…”
Section: Introductionmentioning
confidence: 98%